Dilemma of presymptomatic testing in children with history of late onset neurodegenerative spinocerebellar ataxia in Indonesia - Nydia Rena Benita Sihombing; Tri Indah Winarni; Maria Belladonna; Annastasia Ediati; Sultana MH Faradz (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Spinocerebellar ataxia (SCA) is a late onset neurodegenerative disorder in which coordination and balance are affected. Although many international guidelines have been established regarding presymptomatic testing, it is still a grey area in Indonesia. We report two large families with advanced stages of SCA who underwent presymptomatic genetic testing in children along counseling process.Case presentation: Thorough examination was performed, including pedigree construction, physical and neurological examination, gene mutation analyses for patients, and presymptomatic testing for family members, including children. SCA3/MJD1 gene mutation analysis was done in both cases, and a full penetrance CAG repeat expansion was found in both affected patients. Two different outcomes were observed in the offspring, who were both children. The risk and consequences of positive results had been explained in a counseling session to family members, who decided to keep the information until the child would have reached legally adult age.Conclusions: In developing countries such as Indonesia, problems arose due to ethical issues, knowledge of genetic diseases, and inaccessible molecular diagnostics. Culture, religion and tribe diversities may create additional challenges. These cases emphasize the need for careful consideration of presymptomatic testing in children, especially in complicated situations where psychological and ethical issues should be addressed.